Frequency of Verbal Forms and Language Standard - Galeev, Timur I.; Habibulina, Elena V. (Journal of History Culture and Art Research, 2017)
The article offers the description of a modern experiment, which gives the possibility of complex information extraction about the cognitive structure of the linguistic evolution of Language Standart (Norm). The study was conducted using the Google Books Corpus, which provides unprecedented opportunities for linguistic studies. The purpose of the experiment was to identify the patterns of competing forms evolution within the center of the verbal paradigm (3Sg and 3Pl) on the basis of the data concerning the frequency of their use. The study was conducted on the material of excess verb forms with the variability of a/o vowels in a root (обусловливать/обуславливать). The graphs for variable word form competition clearly illustrate that the process of norm change consists of stages, each of which has numerical characteristics of two competing word form use. The chronological frameworks for an inflectional model change are established with the accuracy of up to 10 years. The graphs obtained as the result of the experiment make it possible to conclude that almost half of the verbs were not variative, although they previously considered. During the discussion of the obtained empirical data, a conclusion is made about the morphemic structure of a word, in which a root vowel changes. Possessing the information about similar processes in other verb paradigms, researchers are able to predict a possible change of inflectional models in the future and, as a consequence, the fixing of a new norm in lexicographical, orthographic and orthoepic sources.